(untitled) (Вісник Кримінологічної асоціації України, 2022)
The article discusses the main countries where there is a national legislation on cruelty to animals. The main structures in the criminal codes and administrative codes on responsibility for such criminal offenses are considered. Conclusions are drawn on the optimization of Ukrainian legislation on this topic. Нhe legislation of foreign countries is very colorful, heterogeneous and differs in approaches to protecting animals from cruel treatment. The legislation of EU member states is the most developed. Wide use of the causal approach in the construction of criminal law norms is noted, which partially reduces the level of their blanketness and simplifies their application. At the same time, in all the mentioned foreign countries, the category of "cruel treatment" remains open to interpretation, referring to the basic normative legal acts in the field of animal protection to clarify the spirit of the law. The same approach is characteristic of Ukrainian criminal legislation, in particular, in terms of changes and additions to Art. 299 of the Criminal Code of Ukraine in the direction of detailing individual manifestations of cruelty to animals. And this genesis will continue in the future